The Despost`s Apprentice. Donald Trump`s Attack on Democracy de Brian Klaas - Díaz González, José Andrés (Centro de Investigación en Cultura y Desarrollo (CICDE), 2018)
Reseña del libro:The Despost`s Apprentice. Donald Trump`s Attack on Democracy de Brian Klaas